2001
DOI: 10.1002/app.1689
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, thermomechanical, and electrochemical characterization of the organic–inorganic hybrids poly(ethylene oxide) (PEO)–silica and PEO–silica–LiClO4

Abstract: ABSTRACT:To study the effect of the silica content on the properties of the salt-free and salt-added hybrids based on poly(ethylene oxide) (PEO) and silica, two series of hybrids, PEO-silica and PEO-silica-LiClO 4 (O:Li, 9:1) hybrids were prepared via the in situ acid-catalyzed sol-gel reactions of the precursors [i.e., PEO functionalized with triethoxysilane and tetraethyl orthosilicate (TEOS)]. The morphology of the hybrids was examined by scanning electron microscopy (SEM) of the fracture surfaces of the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…Coulombic interactions as suggested by spectroscopy and DSC studies [6][7][8][9][10][11][12][13]. Further increase in the [Li/O] value led to a decrease in the conductivity probably due to the immobilization of the polymer chains via 0-Li + -0 cross-linking [6][7][8][9][10][11][12][13]. The present group has also reached the similar conclusion by direct determination of ionic mobility and hence the mobile ion concentration [11,12].…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…Coulombic interactions as suggested by spectroscopy and DSC studies [6][7][8][9][10][11][12][13]. Further increase in the [Li/O] value led to a decrease in the conductivity probably due to the immobilization of the polymer chains via 0-Li + -0 cross-linking [6][7][8][9][10][11][12][13]. The present group has also reached the similar conclusion by direct determination of ionic mobility and hence the mobile ion concentration [11,12].…”
Section: Methodssupporting
confidence: 80%
“…The structural studies were carried out using a Hitachi scanning electron microscope (model S-4300) and a Bio-Rad FT-IR spectrometer (model: FT-165, range: 400-4000 cm" 1 , resolution: 2 cm" 1 ). Coulombic interactions as suggested by spectroscopy and DSC studies [6][7][8][9][10][11][12][13]. Further increase in the [Li/O] value led to a decrease in the conductivity probably due to the immobilization of the polymer chains via 0-Li + -0 cross-linking [6][7][8][9][10][11][12][13].…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…24,25 It has been reported that T g temperatures of polymers containing silica depend on the silica content. [26][27][28] This dependence was observed only in those cases where the polymer is not chemically bound to the silica lattice. In hybrids, the reaction between DCN units and silica results in formation of SiAOASi units.…”
Section: Thermal Transitionsmentioning
confidence: 77%
“…5 There are many reports on the preparation of hybrid composite materials that have been formed by adopting this approach. [1][2][3][4][5][6][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In addition to polymer/silica hybrids, other hybrid composites based on elements such as Ti, Zr, and Al have also been reported. [28][29][30][31][32][33][34][35][36] The synthesis of hybrid systems requires a strategy wherein the formation of good composites arises from components that are well suited to each other.…”
Section: A Key Parameters For Forming Nanohyhybridsmentioning
confidence: 99%